Sporadic cases of acute autochthonous hepatitis E virus infection in Southwest Germany - Brost, Sylvia; Wenzel, J. J.; Ganten, Tom M.; Filser, Michael; Flechtenmacher, Christa; Boehm, S.; Astani, Akram; Jilg, W.; Zeier, Martin; Schnitzler, Paul (Clinical and diagnostic virology, 2010)
Hepatitis E infection is usually a self-limiting disease and an important cause of acute hepatitis in tropical and subtropical regions where the virus is endemic. In industrialized countries, sporadic cases of acute hepatitis E virus (HEV) infections have been described and the number of documented autochthonous infections seems to be increasing. We report three sporadic cases of autochthonous hepatitis E infections in Southwestern Germany which presented at our university hospital within two years. All cases were men who presented with acute hepatitis, icterus and elevated liver. In case 1 and case 2, liver biopsy revealed acute hepatitis, both patients were positive for anti-HEV antibodies, case 1 was also positive for HEV RNA with a viral load of 3.0×103copies/ml in serum. In case 3, anti-HEV antibodies were detectable and HEV RNA was detected in serum (4.3×103copies/ml) and stool (1.4×106copies/ml). None of the patients had a recent travel history outside Germany and close contact to animals has been denied. HEV sequence analysis of two patients revealed genotype 3 with homologies to other European isolates and isolates from swine. Thus the source of infection remains unclear. Hepatitis E should be considered in differential diagnosis in patients with unexplained hepatitis and patients with acute hepatitis, whatever their age or travel history might be, should be tested for HEV.
Erstmals am 11. November 2009 online veröffentlicht
Gesehen am 01.03.2023